THE EVOLUTION OF FOUCAULT'S REASONING ON PATHOLOGY - Kozlovs, Normunds; Skulte, Ilva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This paper is an attempt to theoretically describe the development and transformation of the ideas of French philosopher Michel Foucault whose work on body, disease and mental illness provide a basis for an advanced approach in the philosophy of medicine. The aim of the research is to understand on the basis of the theoretical review of Foucault’ s works and secondary literature the evolution of the reasoning on pathology in different works by the French author. In the first part of the paper we describe how Foucault came to the idea that psychiatric and organic must be treated as completely different. In the second part, we ad more sociocultural context and discuss Foucault’s ideas in the perspective of developing modernity.